Mycoplasma penetrans urethritis in men. A case–control study - Piñeiro, Luis; Idigoras, Pedro; Manzanal, Ayla; Ansa, Iñigo; Vicente, Diego (Frontiers in Microbiology, 2025)
IntroductionA microbiological diagnosis is not reached in many urethritis cases, the proportion varying with the diagnostic methods and targets available. Mycoplasma penetrans is an emerging pathogen, recently described as a possible aetiological agent in urethritis, especially in men who have sex with men (MSM) and persons living with HIV.MethodsBetween June 2021 and June 2024, urethral samples from men were analysed for the presence of M. penetrans using an in-house real-time PCR, and for other sexually transmitted infections with standard techniques (gram stain, culture, PCR, and serology). Three groups were studied, one comprising 55 consecutive cases of urethritis in which the infectious aetiology had not previously been identified, and two randomly obtained control groups: 102 patients with microbiologically-identified urethritis, and 91 patients with no manifestations of urethritis and no pathogen detected.Results and discussionM. penetrans DNA was detected in 7/55 (12.7%) of the idiopathic urethritis cases, but not in any of the controls (p < 0.001). None of the M. penetrans-positive patients had HIV infection and six were MSM. The results from this study indicate an association between infection by M. penetrans and urethritis in men. Therefore, the use of techniques for detecting M. penetrans could help bridge the diagnostic gap in idiopathic urethritis.